Chinese multicentre prospective registry of breast cancer patient-reported outcome-reconstruction and oncoplastic cohort (PRO-ROC): a study protocol. Issue 12 (15th December 2019) - Li, Lun; Yang, Benlong; Li, Hongyuan; Yin, Jian; Jin, Feng; Han, Siyuan; Liao, Ning; Shi, Jingping; Ling, Rui; Li, Zan; Ouyang, Lizhi; Wang, Xiang; et al.
Abstract : Introduction: Available patient-reported outcome (PRO) studies are mainly from single institution or of small sample size, and the variations across hospitals and regions were not fully analysed. A multicentre, prospective, patient-reported outcome-reconstruction and oncoplastic cohort (PRO-ROC) will be planned to assess the PROs of Chinese patients with breast cancer who will undergo breast reconstruction (BR) or oncoplastic breast-conserving surgery (OBCS). Methods and analysis: The inclusion criteria are female patients with breast cancer aged >18 years old who will undergo BR or OBCS. This cohort will include at least 10 000 consecutive patients (about 5000 patients who will undergo BR and 5000 patients who will undergo OBCS). The exposures were surgery types: BR and OBCS regardless of the techniques and materials used. The primary endpoint will be PROs, which include BREAST-Q and quality of life (European Organisation for Research and Treatment (EORTC) Quality of Life Questionnaire Core 30 (QLQ-C30) and EORTC QoL Breast Cancer-specific version (QLQ-BR23)). All patients will be followed up to 24 months after operations. All data will be prospectively collected using an app software. Data will be analysed using SPSS and Stata software. Ethics and dissemination: This study follows the Helsinki Declaration. All patients will be asked to sign an informed consent before enrolment. The results of this study will be presented at national and international meetings and published in a scientific peer-reviewed journal. Trial registration number: NCT04030845; Pre-results .